Chapter Graphene and Active Metamaterials: Theoretical Methods and Physical Properties - Mattheakis, Marios (InTechOpen, 2017)
Protective immune defences are dependent upon critical roles played by dendritic cells (DCs), rendering them important targets for both vaccine delivery and virus infection. Studies in these areas led to successful development of targeted vaccine delivery, including synthetic virus-like particle (SVLP) and nanoparticulate RNA vaccines. A major consideration is DC endocytosis, whereby the different endocytic routes influencing the outcome. Rapid clathrin-mediated endocytosis likely favours degradative pathways. Slower processes such as macropinocytosis, caveolar endocytosis and retrograde transport to endoplasmic reticulum relate more to the processing rates leading to antigen presentation by DCs. These pathways are also influential in promoting the initiation of virus replication following infection. DC endocytosis of RNA viruses and RNA vaccines must lead to cytosolic translocation of the RNA for translation, relating to the process of antigen cross-presentation. One can learn from observations on both virus infections and cross-presentation for delivering RNA vaccines. Accordingly, recent advances in nanoparticulate delivery have been applied with self-amplifying replicon RNA (RepRNA), providing efficient delivery to DCs and promoting replicon-encoded antigen translation. Through realising the important relationships between DC endocytic pathways and induction of immune responses, delivery of SVLP and RepRNA vaccines to DCs offers high value for the development of future synthetic vaccine platforms.